Students Self-Assessment of Demonstration-Based Flipped Classroom on Senior Secondary School Students’ Performance in Physics - Abosede, Peter Joy; Onasanya, Samuel A.; Ngozi, Okonkwo Clementina (Universitas Pendidikan Indonesia (UPI), 2024)
The purpose of this study was to investigate students' self-assessment demonstration-based flipped classroom instructional strategies on pre-degree students' achievement in Physics in the Ilorin metropolis. A quasi-experimental non-equivalent pretest-posttest control group design was performed to measure the effect of flipped classrooms on high school physics performance using a mixture of qualitative and quantitative methods. The sample included two specially selected intact physics classes of Advanced Level II (S.S. 2), each containing 30 participants. The experimental group was taught using a flipped classroom model and the control group was taught using conventional teaching methods. Studies have found no significant difference in performance between students taught using a demonstration-based flipped classroom and students taught using traditional methods. As a result, it was found that the use of demonstration classes did not significantly affect the improvement of students' academic performance. The study also found that some students felt confident that they were responding positively on pretests and posttests to their flipped curriculum performance. It was recommended to conduct physics teaching and learning in an engaging and learner-centered manner, and demonstration-based-flipped learning instructional strategy should be adopted and encouraged among teachers and students.